Multi-Criteria Methods and Techniques Applied to Supply Chain Management 2018
DOI: 10.5772/intechopen.74067
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Criteria Decision-Making Methods Application in Supply Chain Management: A Systematic Literature Review

Abstract: Over the last decade, a large number of research papers, certified courses, professional development programs and scientific conferences have addressed supply chain management (SCM), thereby attesting to its significance and importance. SCM is a multi-criteria decision-making (MCDM) problem because throughout its process, different criteria related to each supply chain (SC) activity and their associated sub-criteria must be considered. Often, these criteria are conflicting in nature. For their part, MCDM metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 125 publications
0
33
0
2
Order By: Relevance
“…Besides SAW, TOPSIS is revealed as the most used method to assess MCDM problems in different fields, such as supplier selection [123], manufacturing and product recovery [124], supply chain management [125], or material selection in the automotive industry [126], just to cite some examples. After analysing the use of MCDM in other fields of application, it shall be concluded that the trends detected in the field of sustainability assessment of infrastructures are quite similar to those popular in other fields.…”
Section: Aggregation Of Indicatorsmentioning
confidence: 99%
“…Besides SAW, TOPSIS is revealed as the most used method to assess MCDM problems in different fields, such as supplier selection [123], manufacturing and product recovery [124], supply chain management [125], or material selection in the automotive industry [126], just to cite some examples. After analysing the use of MCDM in other fields of application, it shall be concluded that the trends detected in the field of sustainability assessment of infrastructures are quite similar to those popular in other fields.…”
Section: Aggregation Of Indicatorsmentioning
confidence: 99%
“…AHP and DEA are two leading MCDA methods by the number of applications and publications (Khan et al., 2015). Then, AHP and DEA were first considered to be applied to this work, since application of both methods provides an assessment index, ranging from 0 to 1.…”
Section: Introductionmentioning
confidence: 99%
“…MCDM techniques can then deal with the multicausality nature of the bullwhip effect problem, which can be represented by a set of criteria related to the main causes of this phenomena: demand forecasting updating, order batching, price fluctuations, gaming, and rationing. In addition, the use of AHP and DEMATEL methods enable supply chain managers to design both short-term and long-term strategies based on linear dependency, interdependence, and feedback so that bullwhip effect management can be facilitated (Khan, Chaabane, & Dweiri, 2018;Ortiz-Barrios et al, 2017;Ortiz-Barrios et al, 2018;Wu & Tsai, 2012). This is complemented by the use of TOPSIS, which can calculate the gap between the current performance of bullwhip-phenomena-related criteria and the desired target (Saeida Ardakani, Nejatian, Farhangnejad, & Nejati, 2015;Shukla, Agarwal, Rana, & Purohit, 2017).…”
Section: Perspectives On Bullwhip Effectmentioning
confidence: 99%